Market orientation and corporate social responsibility: towards an integrated conceptual framework - Mahmoud Abdulai Mahmoud; Charles Blankson; Robert E. Hinson (International Journal of Corporate Social Responsibility, 2017)
Abstract The aim of this study is to develop a comprehensive framework and propositions showing the integration of market orientation (MO) as an economic-oriented strategy and corporate social responsibility (CSR), as a socially–oriented strategy for business performance (BP). A review of literature on the three constructs of  MO,  CSR and BP facilitated the development of the framework and a number of research propositions. An integrated conceptual framework of economic and social strategies is constructed based on prior conceptualisation of MO and CSR. In total, twenty-six (26) propositions are developed based on the integrated conceptual framework. An empirical examination of the model will clarify further, relations among the variables and then authenticate the developed model and propositions. The study provides practitioners with a framework and the accompanying propositions for decision making with respect to their strategic choices and performance. The conceptual framework and the proposition developed when implemented are expected to enhance both the firm and customer value which has a wider implication for the society. The novelty in this research is the common antecedents of both MO and CSR. This research augments the few studies on the integration of MO and CSR.